An analysis of the suitability of selected newspaper material as a teaching resource in efl courses - Arellano, César (2010)
This research has as principal theme, the use of selected newspaper as a teaching resource in EFL courses and their innovate performance in our country, taking experiences from other countries and trying to adapt them into our educational reality. If we speak of newspaper, we can say that it is in the reach of almost everybody. Then it is a resource that is beside of us and we can use it to change the classroom material into one more dynamic, also it let us select attractive themes to our students. We have found in a couple of countries like United States and Canada lot of experiences in the use of newspaper. They have created a campaign which is called NIE (Newspapers in Education). This initiative encourages the use of newspapers as an educational tool both to complement and supplement traditional classroom texts and resource materials.